The role of facultatively nectarivorous birds as pollinators of Anarthrophyllum desideratum in the Patagonian steppe: a geographical approach - Paiaro, Valeria (2017)
The endemic shrub Anarthrophyllum desideratum appears to be the only ornithophilous plant offering nectar as reward in the extensive Patagonian steppe. The identity of its floral visitor assemblage and to what extent this species depends on bird pollination for sexual reproduction is yet unknown. A. desideratum’s vast distribution includes climatic gradients, which may promote geographical shifts in its floral visitors. The aims of this study were to determine the species dependence on pollinators to set fruits, to identify its floral visitor assemblages, to document possible geographical and environmental variation of these assemblages across the species range and to assess their temporal constancy. We conducted different pollination treatments in several populations to assess the species breeding system. Floral visitors were identified in 18 populations distributed along the entire species range and their visitation frequencies were quantified over three flowering periods. We found that the species is self-compatible and that floral visitors do not contribute to fruit set in two marginal populations. Fruit set of open pollinated plants significantly differed among populations, which suggests that the species dependence on pollinators varies among sites. Eight species of non-exclusively nectarivorous birds, mostly passerine, were observed visiting flowers arranged in different assemblages across the species range. Population differences in the proportion of visits by the two most abundant bird species remained constant over time. Geographical differences of bird assemblages were not spatially structured and were weakly associated with climate of the flowering period, suggesting that climatic gradients would not be important as drivers of the geographical variation in A. desideratum’ floral visitors. Our results indicate that non-exclusively nectarivorous birds visit flowers of A. desideratum, revealing for first time the facultative nectarivory behaviour of these bird species in the Patagonian steppe. The potential role of such bird visitors as pollinators of A. desideratum appears to vary geographically